2013
DOI: 10.3389/fmicb.2013.00175
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial and structural dynamics in aerobic granular biofilms

Abstract: Aerobic granular sludge (AGS) is based on self-granulated flocs forming mobile biofilms with a gel-like consistence. Bacterial and structural dynamics from flocs to granules were followed in anaerobic-aerobic sequencing batch reactors (SBR) fed with synthetic wastewater, namely a bubble column (BC-SBR) operated under wash-out conditions for fast granulation, and two stirred-tank enrichments of Accumulibacter (PAO-SBR) and Competibacter (GAO-SBR) operated at steady-state. In the BC-SBR, granules formed within 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 82 publications
3
102
0
Order By: Relevance
“…FITC-ConA and Alexa647-ConA also successfully stained the aggregate matrix at concentrations as low as 100 lg/mL (Figs. 4d, 7), which was expected as lectin stains have been explored in considerable depth for staining EPS in biofilms (Neu et al 2001;Strathmann et al 2002), river snow (Neu 2000;B€ ockelmann et al 2002), and sludge aggregates (McSwain et al 2005;Weissbrodt et al 2013). Compared to Alcian Blue, FITC-ConA/Alexa647-ConA covered similar areas of the aggregate matrix but stained slightly distinctive features.…”
Section: Visualization and Imaging Of The Aggregate Matrixmentioning
confidence: 95%
“…FITC-ConA and Alexa647-ConA also successfully stained the aggregate matrix at concentrations as low as 100 lg/mL (Figs. 4d, 7), which was expected as lectin stains have been explored in considerable depth for staining EPS in biofilms (Neu et al 2001;Strathmann et al 2002), river snow (Neu 2000;B€ ockelmann et al 2002), and sludge aggregates (McSwain et al 2005;Weissbrodt et al 2013). Compared to Alcian Blue, FITC-ConA/Alexa647-ConA covered similar areas of the aggregate matrix but stained slightly distinctive features.…”
Section: Visualization and Imaging Of The Aggregate Matrixmentioning
confidence: 95%
“…Most studies investigate the effects of operational parameters by analyzing the community composition in samples obtained at a single sampling date during steady-state operation (e.g., Ebrahimi et al, 2010; Gonzalez-Gil and Holliger, 2011; Cydzik-Kwiatkowska, 2015). Only a few reports assess the temporal variation of the microbiome (Li et al, 2008; Weissbrodt et al, 2013; Lv et al, 2014). However, steady-state process performance does not necessitate stable microbial community composition: long-term studies of full-scale activated sludge treatment plants revealed strong variation in the bacterial population and a gradual succession away from initial conditions (Wells et al, 2011; Fredriksson, 2013; Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the EPS carbohydrates could be approached using fluorescence lectinbinding analysis (FLBA) which detects glycoconjugates and their distribution within the biofilm (Figure 10(C), and S1) (Marchal et al, 2011;Neu & Lawrence, 2014bTuronova et al, 2016;Zippel & Neu, 2011). Characterization of EPS carbohydrate using FLBA depends on the specificity of the lectins used (Weissbrodt et al, 2013;Zhang et al, 2015a). Conventional fluorescence-labeled probes detected with fluorescence correlation spectroscopy (FCS) for the overall structure of the biofilm could be also employed to assess the viscosity and porosity of the biofilm (Peulen & Wilkinson, 2011).…”
Section: Measurement Of Eps Componentsmentioning
confidence: 99%